Assessing Implementation of Managerial Accounting Practices: Perspective of Pakistani SMEs - Zehra, Iffat; Ahmed, Farhan (Esensi: Jurnal Bisnis dan Manajemen, 2019)
With increasing production cost and growing local and international competition, accountants within Small and Medium Enterprises (SMEs) are largely encumbered with the onus of cost control. Through this paper, we empirically examine use and perceived importance of cost management accounting practices within Pakistani manufacturing SMEs. The cross-sectional study is conducted under descriptive research design. Findings from survey questionnaire of 44 manufacturing SMEs indicate that process costing method is widely used and complexity in production process is main difficulty faced by SMEs in product costing. Descriptive analysis indicates that SMEs mainly use product costing information to make pricing decisions of products, profitability calculation and in decision making for new products. SMEs prefer to employ conventional tools like planning and control, budgeting and strategic planning for decision making purposes. Limited sample size under descriptive analysis restricts applicability and generalizability. Our study makes novel contribution in the domain of cost management practices in SMEs since majority of literature is available on cost management practices adopted by only large corporates within Pakistan.